OUTPATIENT WAITING TIME AND PATIENT SATISFACTION AT THE OUTPATIENT DEPARTMENT OF NGHE AN EYE HOSPITAL IN 2025 (Vietnam Journal of Community Medicine, 2026)
Objective: To evaluate outpatient waiting time, patient satisfaction, and related factors at the Outpatient Department of Nghe An Eye Hospital in 2025.Methods: A cross-sectional descriptive study was conducted among 250 outpatients attending the Outpatient Department of Nghe An Eye Hospital from April to September 2025. Data were collected through face-to-face interviews combined with direct measurement of time spent at each step of the examination process. Patient satisfaction was assessed using a three-level scale. Data were analyzed using SPSS version 20.0 with descriptive statistics and chi-square tests; statistical significance was set at p < 0.05.Results: Females accounted for 58.0% of participants, and patients aged over 50 years comprised the largest proportion (42.4%). Mean examination time increased with the number of paraclinical services, from 20 minutes for consultation only to 85 minutes for those undergoing three or more services. Overall, 76.0% of patients reported being satisfied or very satisfied. The proportion of dissatisfaction was significantly higher among patients receiving two or more paraclinical services compared with those receiving fewer services (32.6% vs. 13.4%; p < 0.05), and among those with examination time ≥60 minutes compared with
Keywords: outpatient waiting time; patient satisfaction; outpatients; eye hospital.